Dynamics of medical and statistical indicators of cervical cancer over a 10-year period (2011–2020) in Novokuznetsk - S. V. Shramko; N. M. Zhilina; V. N. Dureev (Опухоли женской репродуктивной системы)
Background. Cervical cancer is considered one of the most common and socially significant cancers of the female reproductive system. Despite the visual localization of the tumor, every second case is diagnosed at stage III–IV of the disease, when little can be done to help the patient, whereas early detection of the disease could help save the life and working capacity of young women.Aim. To analyze the incidence of cervical cancer in Novokuznetsk for the period 2011–2020 by age groups and identify areas of risk for the development of the disease in order to develop effective and timely measures for early diagnosis.Materials and methods. A database was formed on the basis of statistical reports of the Regional Clinical Oncological Dispensary (Novokuznetsk branch) for 2011–2020 with a unit of observation of 1 year, for some indicators, information is provided since 2008. The database analysis was carried out in the licensed statistical package IBM SPSS Statistics 19 using the following methods: Kendall’s tau correlation method (Ʈ), calculation of median values of indicators, upper and lower quartiles, Mann–Whitney test (U).Results. In residents of Novokuznetsk for the period 2011–2020 a statistically significant increase in both absolute and relative (per 100,000 population) cervical cancer incidence was revealed. The risk zone for cervical cancer is 40– 44 years old.Conclusion. When conducting preventive examinations and medical examinations of women, one should focus on the identified risk zone for cervical cancer. Conducting adequate and timely medical examinations seems to be a resource measure that contributes to the preservation of the life and health of women.